2002
DOI: 10.1046/j.1439-0264.2002.00364.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of the Ultimobranchial Gland to Vitamin D3 Treatment in Freshwater Mud Eel, Amphipnous cuchia, Kept in Different Calcium Environments

Abstract: Freshwater mud eel, Amphipnous cuchia, were injected intraperitoneally daily with 100 ng of vitamin D3/100 g body weight and maintained in media containing either no calcium or different calcium concentrations. The eels were killed after 1, 3, 5, 10 and 15 days following the treatment and their serum calcium levels were measured. The ultimobranchial glands were fixed and processed using the routine paraffin method for histological studies. The results of the present study indicate that vitamin D3 can induce hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…The plasma calcium is restored and is elevated after day 10 and day 15 in vehicleinjected H. fossilis kept in calcium-deficient freshwater. An increase in the plasma calcium content after acclimation of the fish to low ambient calcium/calcium-deficient freshwater has also been recorded by Wendelaar Bonga et al (1985), , Singh and Srivastav (1996) and Srivastav et al (2002). The present study supports this conclusion as in calcium-deficient freshwater; the prolactin cells of H. fossilis became hyperactive.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The plasma calcium is restored and is elevated after day 10 and day 15 in vehicleinjected H. fossilis kept in calcium-deficient freshwater. An increase in the plasma calcium content after acclimation of the fish to low ambient calcium/calcium-deficient freshwater has also been recorded by Wendelaar Bonga et al (1985), , Singh and Srivastav (1996) and Srivastav et al (2002). The present study supports this conclusion as in calcium-deficient freshwater; the prolactin cells of H. fossilis became hyperactive.…”
Section: Discussionsupporting
confidence: 91%
“…The ultimobranchial gland of H. fossilis became hyperactive in response to administration of prolactin to the fish kept either in artificial freshwater or calciumdeficient freshwater. Similar observations about the activity of fish ultimobranchial gland in response to experimental hypercalcemia have been reported in past by several investigators (Lopez et al, 1968;Chan, 1972;Peignoux-Deville et al, 1975;Swarup and Srivastav, 1984;Srivastav et al, 1997Srivastav et al, , 2002. The studies of Fouchereau-Peron et al (1986) support the observations of the foregoing study as they have reported that transfer of trout from freshwater to sea water induces the gland to synthesize and secrete more calcitonin which results into a two-fold increase in the plasma calcitonin level.…”
Section: Discussionsupporting
confidence: 87%